Gyrodactylus jarocho sp. nov. and Gyrodactylus xalapensis sp. nov. (Platyhelminthes: Monogenea) from Mexican poeciliids (Teleostei: Cyprinodontiformes), with comments on the known gyrodactylid fauna infecting poeciliid fish - Rubio-Godoy, Miguel; Paladini, Giuseppe; García-Vásquez, Adriana; Shinn, Andrew P. (Zootaxa, 2010)
Poeciliid fish have been dispersed worldwide with the ornamental fish trade and as part of mosquito control programmes, and with them their gyrodactylid parasites. Due to the easy maintenance and reproduction in aquaria of both poeciliid fish hosts and gyrodactylid parasites, several ecological, epidemiological and parasitological studies have been made with them. To date, nine species of Gyrodactylus are known to infect poeciliid fish: Gyrodactylus bullatarudis Turnbull, 1956, Gyrodactylus costaricensis Kritsky & Fritts, 1970, Gyrodactylus cytophagus Paperna, 1968, Gyrodactylus gambusiae Rogers & Wellborn, 1965, Gyrodactylus milleri Harris & Cable, 2000, Gyrodactylus pictae Cable, van Oosterhout, Barson & Harris, 2005, Gyrodactylus poeciliae Harris & Cable, 2000, Gyrodactylus rasini Lucký, 1973, and Gyrodactylus turnbulli Harris, 1986. We describe two new gyrodactylid species from wild Mexican poeciliid fish collected within their native distribution ranges: Gyrodactylus jarocho sp. nov. from Xiphophorus hellerii Heckel and Gyrodactylus xalapensis sp. nov. from Heterandria bimaculata Heckel, the first gyrodactylid to be described from this host. We also present a new host and locality record for G. bullatarudis, which was found on Poecilia mexicana Steindachner. Mexican samples were compared with museum specimens of all known gyrodactylids from poeciliid hosts, which were subjected to morphometric analysis. Both new species were clearly separated from all other known gyrodactylids infecting poeciliid fish in principal components analyses (PCA). Marginal hook sickle morphology is the key to the separation and discrimination of all the gyrodactylids parasitizing poeciliids, and we provide graphical and morphological data to distinguish between the eleven described gyrodactylid species from poeciliid hosts; we hope this proves a practical tool to discriminate between these otherwise morphologically similar parasites. Finally, we present a re-description of the marginal hooks of G. milleri, because re-examination of the holotype demonstrated the presence of three differently-shaped marginal hook sickles. This is the second known species of Gyrodactylus to have noticeably differently-shaped and sized marginal hooks.